The Evaluation Of Nurses' Perception, Capability, And Adequacy Of Training About Spirituality And Spiritual Care In Genaveh Hospitals - Ebrahim Shafiee; Fazlollah Mousavi; Mahdi Gharasi Manshadi; Nayeb Fadaei Dehcheshmeh; Alireza Bibak; Mohammad Azmal (Tehran University of Medical Sciences, 2015)
Background and Aim : Nurses' perception of spirituality can affect the way they behave and communicate with patients in line with spiritual care provision. The present study aims to investigate nurses' perception , capability, and adequacy of training about spirituality and spiritual care in Genaveh hospitals affiliated to Bushehr University of Medical Sciences (BUMS) . Materials and Methods: A cross-sectional descriptive study was performed among 111 nurses working in BUMS hospitals in 2013. The spirituality and spiritual care scale (SSCRS) was used for data collection, which explores nine aspects of spirituality and spiritual care. Descriptive statistics were used to analyze the data. Results: The overall spirituality and spiritual care was 3.86 (out of 5). Among the nine aspects of need for spirituality, belief in God had the highest mean score, and beliefs and values had the least mean values. About 78.7 % of the participants were confronted with the patients' spiritual needs. Meanwhile, 74.6 % of them noted that the current training about spiritual care was not sufficient . Conclusion: Although most participants were able to meet the patients' spiritual needs, most of the nurses did not know enough about the issues related to spiritual care. Therefore, inclusion of spiritual care in nursing curriculum and holding workshops and training courses in this area can be useful.